2007
DOI: 10.1080/10691898.2007.11889468
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Statistics Education Research in My Classroom

Abstract: A collaborative, statistics education research project (Lovett, 2001) is discussed. Some results of the project were applied in the computer lab sessions of my elementary statistics course. I detail the process of applying these research results, as well as the use of knowledge surveys. Furthermore, I give general suggestions to teachers who want to put educational research results into effective use in their own classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Yet, exactly how a class should be structured and which techniques work best with each other was not considered in this research and would seem to be of importance to instructors wishing to incorporate such styles. Jordan (2007) stressed that the implementation of such instructional styles is open to much interpretation. In fact, some research has indicated that the implementation of these techniques does not always happen.…”
Section: Indicated Thatmentioning
confidence: 99%
“…Yet, exactly how a class should be structured and which techniques work best with each other was not considered in this research and would seem to be of importance to instructors wishing to incorporate such styles. Jordan (2007) stressed that the implementation of such instructional styles is open to much interpretation. In fact, some research has indicated that the implementation of these techniques does not always happen.…”
Section: Indicated Thatmentioning
confidence: 99%
“…• They should be familiar with statistical concepts and methods and have some experience with statistical problems (Larsen, 2006;Jordan, 2007). • They should know the difference between statistical thinking and statistical methods (Garfield, 2002).…”
Section: Introductionmentioning
confidence: 99%